Workload, Work Stress, and Turnover Intention: Unraveling the Influence of Work Satisfaction in Employees: Beban Kerja, Stres Kerja, dan Niat Berpindah: Mengungkap Pengaruh Kepuasan Kerja pada Karyawan - Mokhammad Indra Bagus Prastyo; Dewi Andriani (Academia Open, 2022)
This research aimed to investigate the impact of workload and work stress on work satisfaction, as well as the combined effects of workload, work stress, and work satisfaction on turnover intention among employees of CV. Cahaya Baru. A quantitative approach was employed, utilizing a total sampling method with a sample size of 63 employees. Data collection involved questionnaires and observations, while path analysis using the SPSS 25.0 application program was employed for data analysis. The findings revealed that workload and work stress significantly influenced work satisfaction. Additionally, workload, work stress, and work satisfaction collectively exerted a significant effect on turnover intention. However, workload and work stress did not significantly impact turnover intention through work satisfaction. These results shed light on the complex interplay between workload, work stress, work satisfaction, and turnover intention, emphasizing the importance of addressing work-related factors to enhance employee well-being and reduce turnover rates. Highlights: The study examines the impact of workload and work stress on work satisfaction and turnover intention among employees. Workload and work stress significantly influence work satisfaction, while workload, work stress, and work satisfaction collectively affect turnover intention. The findings emphasize the importance of addressing work-related factors to enhance employee satisfaction and reduce turnover rates. Keywords: workload, work stress, work satisfaction, turnover intention, employees.